Donor‐derived herpes simplex virus hepatitis in a kidney transplant recipient and review of the literature. Issue 3 (2nd February 2021) - Zeidan, Joseph H.; Casingal, Vincent; Hippen, Benjamin; Ahrens, William; Lamm, Kevin; Gerber, David A.; Schmeltzer, Paul A.; Gajurel, Kiran
Abstract: Donor‐derived (DD) herpes simplex virus (HSV) hepatitis in solid organ transplant (SOT) recipients is extremely uncommon but carries a high mortality rate. The diagnosis is challenging due to the non‐specific presentation and lack of clinical suspicion. We report a case of DDHSV hepatitis in a HSV2 pre‐transplant seronegative kidney recipient who received the organ from a HSV2 seropositive donor. The case is highlighted by a few unusual features, namely severe thrombocytopenia and the development of cutaneous, oral and esophageal HSV lesions several weeks after symptom onset while recovering on appropriate treatment. A review of nine proven and probable DDHSV hepatitis cases (including eight previously published ones) showed that fever is a common presenting feature while gastrointestinal symptoms and cutaneous manifestations are uncommon. The symptoms almost always occurred within 2 weeks of transplant. Six out of the nine DDHSV hepatitis patients, including five patients who were on appropriate treatment, died within a month after transplant.